Does female suffrage increase public support for government spending? Evidence from Swiss ballots - Katharina Jaronicki (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Does the enfranchisement of women lead to an increase in public support for government spending? By utilizing a natural experiment from Switzerland, I test this hypothesis empirically. I analyze the voting outcomes of two very similar referendum ballots concerning the federal government's competency to levy income, capital and turnover taxes. The first ballot has taken place shortly before the extension of suffrage to women in February 1971, and the other thereafter. To shed light on the existence of gender gaps in approval for government spending, I first estimate the additional turnout due to the introduction of female suffrage, and then estimate the additional turnout's impact on the percentage of yes votes. Surprisingly, I find that approval for government spending is higher among the male population. To overcome concerns that the results might only hold conditionally on voter participation decisions, I provide additional evidence from a probit analysis of a post-ballot survey. These are conducted for voters and non-voters and confirm that the results extend to the non-voting population. My results complement the findings of previous literature which suggest that in the analysis of gender preference gaps for government expenditure spending categories like e.g. welfare and non-welfare items should be distinguished.
Keywords: J16; H10; D72; 330